Study-related demands, resources and curriculum from students’ perspective: results of a qualitative descriptive study among students in nursing and healthcare in Germany - Ivonne-Nadine Jürgensen; Annike Morgane Nock; Peter Koch; Albert Nienhaus; Corinna-Petersen Ewert (BMC Nursing)
Abstract Background Health-related studies are associated with numerous academic and clinical demands that can lead to stress and mental strain. Therefore, university interventions to promote health and well-being are important. However, the academic sources of stress and resources for the group of nursing and healthcare students have not yet been explored in Germany. The aim of this study is therefore to investigate these factors from the students’ perspective. Methods A descriptive qualitative study was conducted. Findings are based on interviews with students from the Department of Nursing and Management in Germany, carried out between October 2022 and January 2023. The interviews were audio‑recorded, transcribed, and analyzed using qualitative content analysis. Results are presented in a descriptive summary. Results Participants reported performance demands, time pressure, group tasks, peer relationships, as well as organizational factors and ergonomic conditions within learning environments as primary stressors in their studies. Essential resources highlighted by the students included opportunities for personal development, physical activity, peer support, and individual competencies. Health was conceptualized by the interviewees as multidimensional, encompassing mental, physical, and social aspects. Integrate a health module into the curriculum was met with ambivalence among participants; on the one hand, it was perceived as an opportunity to enhance awareness of health and self-care, while on the other hand, there was concern regarding potential overload through mandatory obligations. However, participants agreed that a balanced approach, incorporating structured offerings alongside room for individual autonomy, is essential. Conclusions In summary, this study identified study-related stress factors and their impact on mental well-being from the students’ perspective. The stressors reported by our students largely correspond to those identified in international studies involving nursing students in other countries. The current study is limited by the small sample. However, the findings highlight the importance to create healthy study conditions. Findings are particularly relevant for universities and educators in Germany, who would like to become more aware of the study-related stressors of nursing and healthcare students and discuss suitable preventive measures. Further quantitative research should examine the academic demands and their impact on students’ mental health. A nationwide, representative study would be a valuable next step.